دور الرقابة الجبائية في مكافحة التهرب الضريبي - مزيلط, نصر الدين (My University, 2024)
This dissertation deals with the problem of tax evasion and fraud, where this phenomenon has been analyzed with methods and techniques of their treatment and their relationship with external changes, where all countries file the tax audit as a method of control, using its tools and materials to reduce this problem. However, tax audit cannot eliminate tax evasion and fraud alone, but must be used other means such as using prevention methods before evasion or fraud occurs. And coordination between administrations to obtain necessary information, finally the tax control in Algeria is estimated in terms of evolution of the number of files studied and the results presented, to the conclusion of the effectiveness of this control in Algeria with present some problems that suffer the tax audit.
دراسة حالة –مديرية الضرائب لولاية مستغانم-
Keywords: Tax evasion, tax collection, tax audit.